Sommes-nous tous des néo-keynésiens à la Friedman-Phelps-Lucas maintenant? - Ascah, Louis (L'Actualité économique, 1984)
ABSTRACTThe consumer of economic theories has the choice between many different labels. The exaggerated use of these labels is such way that they are often meaningless and can lead to confusion. These points are illustrated in a brief review of the Keynesian-monetarist debate.